Role of Ayurveda Chikitsha Siddhanta in the Management of Amavata W.S.R. to Rheumatoid Arthritis - A Case Study - Nandi, Arpita; Ghosh, Sukumar (International Research Journal of Ayurveda & Yoga, 2023)
Day by day, musculoskeletal problems are rapidly increasing. Aamvata is the most common one of them due to the impairment of Agni (digestive fire). Amavata is also a challenging and burning issue in medical sciences in the world as well as India. In the present scenario, “Amavata” word has been used extensively in comparison to “Rheumatoid Arthritis” (RA). The Ayurvedic approach toward the treatment of Amavata is the need of the present era as no system is successful in providing the complete cure to this disease. The management of modern sciences includes the use of NSAIDS (nonsteroidal anti-inflammatory drugs, glucocorticoids, diseases-modifying anti-rheumatic drugs, and immunosuppressant therapies, long-term use of which leads to many side effects. Due to the wide spectrum of diseases, much prevalence in society, and the lack of effective medicine, the diseases have been chosen. The aims of this study are to find out the efficacy of Ayurvedic treatment methodically as per the line of management of Amavata. Here, a 28-year-old female patient came to OPD complaining of right Kurpar Sandhi Shula (right elbow joint), Uvaya Parsha Sandhi Shula (bilateral finger joint pain), Angamarda (Bodyache), morning sickness, stiffness. Depend on the clinical features, the patient was given Langhana, Swedan, Virechan, and Basti Karma, followed by oral administration of some Samana Aushadhi. Before treatment, the Report of RA Factor was 262.4, which were reduced to 65.8. These treatments showed remarkable results in swelling, pain, and stiffness, which were reduced with an improved range of movement of joints after almost 4 months of treatment.